Co-MOF-74 Derived Porous Carbon as a Highly Active and Durable Electrocatalyst for Oxygen Reduction Reaction in Alkaline Media. (1st August 2022) - Parkash, Anand; Soni, Hira Lal; Seehar, Tahir Hussain; Larik, Rimsha; Sultan, Syed Haseeb; Qudoos, Abdul; Arain, Adeel Mukhtar
Abstract : Pyrolysis of metal-organic framework (MOF) to generate nanostructured carbon-based materials is a potential approach for creating carbon-based materials. The development of a cobalt-based MOF (Co-MOF-74) and its application to oxygen electrocatalysis are described in this study. In alkaline media, the as-obtained Co-PC-400 catalyst displayed superior catalytic performance with the onset potential (Eo = 0.90 V vs. RHE) and more outstanding durability than a Pt/C (20 wt%). Results show that the catalyst has a lot of promise in fuel cells. The Co-MOF successfully catalyzes due to its more significant onset potential, higher current density, and extended durability.